Age and growth of the Cape knifejaw Oplegnathus conwayi, an endemic South African teleost. Issue 1 (2nd January 2022) - Foster, RM; Childs, A-R; Mann, BQ; Potts, WM
Abstract : The South African spearfishery targets a variety of data-deficient species, which are consequently poorly managed. This study aimed to describe the age and growth of one of these species, the Cape knifejaw, Oplegnathus conwayi, which is endemic to the southern and eastern coasts of South Africa. Monthly biological samples were collected through research spearfishing ( n = 170) and augmented by recreational spearfishers' catches ( n = 135). The results indicated that the O. conwayi population sex ratio was skewed towards males (1M:0.6F). The length- and age-frequency distributions were similar between sexes. Oplegnathus conwayi is a relatively slow-growing species, with a maximum-recorded age of 27 years. No significant differences were observed between male and female growth, with the overall population growth curve being best described as L ( t ) = 697.15(1 − e −0.06(t−6.30) ). The slow growth observed in this species is characteristic of a species that is vulnerable to overexploitation, and accordingly a precautionary approach to future management is recommended.